Jack London au prisme de ses premiers traducteurs et préfaciers français. Entre exotisation et domestication - Véronique Béghain (Transatlantica)
This article investigates the reception, translation and circulation of Jack London’s works in France, as France discovers them in the 1920s and 1930s. It privileges qualitative data and focuses on what commentaries were written by his main translators, Louis Postif and Paul Gruyer, and more marginally by the few women who translated London. Drawing on peritextual elements in particular, and focusing even more specifically on the translators’ prefaces and introductions, it is an attempt to grasp the “translating position” (Berman, 1995 74; my translation) of their authors, who are at the heart of the cultural transfer process.